Determinants of vaccination coverage in rural Nigeria - Meurice Francois P; Alufohai Ewan F; Odusanya Olumuyiwa O; Ahonkhai Vincent I (BMC, 2008)
Abstract Background Childhood immunization is a cost effective public health strategy. Expanded Programme on Immunisation (EPI) services have been provided in a rural Nigerian community (Sabongidda-Ora, Edo State) at no cost to the community since 1998 through a privately financed vaccination project (private public partnership). The objective of this survey was to assess vaccination coverage and its determinants in this rural community in Nigeria Methods A cross-sectional survey was conducted in September 2006, which included the use of interviewer-administered questionnaire to assess knowledge of mothers of children aged 12-23 months and vaccination coverage. Survey participants were selected following the World Health Organization's (WHO) immunization coverage cluster survey design. Vaccination coverage was assessed by vaccination card and maternal history. A child was said to be fully immunized if he or she had received all of the following vaccines: a dose of Bacille Calmette Guerin (BCG), three doses of oral polio (OPV), three doses of diphtheria, pertussis and tetanus (DPT), three doses of hepatitis B (HB) and one dose of measles by the time he or she was enrolled in the survey, i.e. between the ages of 12-23 months. Knowledge of the mothers was graded as satisfactory if mothers had at least a score of 3 out of a maximum of 5 points. Logistic regression was performed to identify determinants of full immunization status. Results Three hundred and thirty-nine mothers and 339 children (each mother had one eligible child) were included in the survey. Most of the mothers (99.1%) had very positive attitudes to immunization and > 55% were generally knowledgeable about symptoms of vaccine preventable diseases except for difficulty in breathing (as symptom of diphtheria). Two hundred and ninety-five mothers (87.0%) had a satisfactory level of knowledge. Vaccination coverage against all the seven childhood vaccine preventable diseases was 61.9% although it was significantly higher (p = 0.002) amongst those who had a vaccination card (131/188, 69.7%) than in those assessed by maternal history (79/151, 52.3%). Multiple logistic regression showed that mothers' knowledge of immunization (p = 0.006) and vaccination at a privately funded health facility (p < 0.001) were significantly correlated with the rate of full immunization. Conclusion Eight years after initiation of this privately financed vaccination project (private-public partnership), vaccination coverage in this rural community is at a level that provides high protection (81%) against DPT/OPV. Completeness of vaccination was significantly correlated with knowledge of mothers on immunization and adequate attention should be given to this if high coverage levels are to be sustained.